2013
DOI: 10.1186/2041-7136-3-26
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland governance in an open system: Protecting transhumance corridors in the Far North Province of Cameroon

Abstract: The mobile pastoral system in the far north region of Cameroon is an excellent example of the paradox of pastoral land tenure, in that pastoralists need secure access to pasture and water, but also flexibility in resource use, i.e. the ability to move elsewhere because of spatio-temporal variation in resource availability. In this paper, we draw from our collective research and development experience with mobile pastoralists and discuss how non-governmental organisations have used ordinances and bureaucratic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
(36 reference statements)
0
35
0
1
Order By: Relevance
“…Rangeland governance should be integrated at local, regional, national, and international scales. The Lake Chad Basin Committee (LCBC), for example, governs and supports livestock mobility at national and international levels within the Chad Basin (Moritz et al 2013a). The challenge will be to find the right balance to solve the ''paradox of pastoral land tenure' ' (Ferná ndez-Giménez 2002), which is that pastoralists need secure access to pasture and water, but also flexibility in resource use, i.e., the ability to move elsewhere because of spatiotemporal variation in resource availability (Niamir-Fuller 1999;Turner 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Rangeland governance should be integrated at local, regional, national, and international scales. The Lake Chad Basin Committee (LCBC), for example, governs and supports livestock mobility at national and international levels within the Chad Basin (Moritz et al 2013a). The challenge will be to find the right balance to solve the ''paradox of pastoral land tenure' ' (Ferná ndez-Giménez 2002), which is that pastoralists need secure access to pasture and water, but also flexibility in resource use, i.e., the ability to move elsewhere because of spatiotemporal variation in resource availability (Niamir-Fuller 1999;Turner 1999).…”
Section: Discussionmentioning
confidence: 99%
“…AN OPEN PROPERTY REGIME I next describe the open property regime of pastoralists in the floodplain as I have come to understand it, drawing on a number of my previous publications (Moritz et al 2013a,b, 2014a,b, Moritz 2016. Given the extensive research of social and ecological systems, I would argue that this description is a more accurate description of the current state of pastoralists' management of common-pool grazing resources in the Logone floodplain than that presented by Haller et al (2013).…”
Section: Misfit In the Precolonial Periodmentioning
confidence: 99%
“…Fourth, we showed that economic inequality did not undermine the system of open access (Moritz et al 2015b). Fifth, we discussed the implications of our findings for the governance of rangelands (Moritz et al 2013a (Gulliver 1951), and the Pashtun in western Afghanistan (Glatzer 1977). Thus, the case of pastoralists' management of open access to common-pool grazing resources in the Logone floodplain is not unique.…”
Section: Longitudinal Study Of a Pastoral Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various 'levers' for affecting the model's dynamics are conceivable, an obvious option is to find a proper institutional setting that induces agent interactions toward a more desirable direction. In the context of African pastoralism, institutional matters have most often been discussed with regard to land ownership and land use in ASALs (Lane & Moorehead, 1994;Moritz et al, 2013;Musembi & Kameri-Mbote, 2013;Niamir-Fuller, 1999). As the first step toward a more comprehensive treatment of this subject, some of the standard (and often controversial) rangeland interventions are examined in the simulated drylands.…”
Section: Manipulating Institutional Settingsmentioning
confidence: 99%